Minimal scalar sector of 3-3-1 models without exotic electric charges (2003)
ABSTRACT: We study the minimal set of Higgs scalars, for models based on the local gauge group SU(3)c⊗SU(3)L⊗U(1)X which do not contain particles with exotic electric charges. We show that only two Higgs SU(3)L triplets are needed in order to properly break the symmetry. The exact tree-level scalar mass matrices resulting from symmetry breaking are calculated at the minimum of the most general scalar potential, and the gauge bosons are obtained, together with their couplings to the physical scalar fields. We show how the scalar sector introduced is enough to produce masses for fermions in a particular model which is an E6 subgroup. By using experimental results we constrain the scale of new physics to be above 1.3 TeV.